Determinan permintaan deposito berjangka di Indonesia - Putra Artama, Dandi; Nurjanah, Rahma; Vyn Amzar, Yohanes (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This study aims to determine the proportion of time deposits to third party funds and what are the factors that influence the demand for time deposits in Indonesia in 1995-2021. The data used in this study is secondary data sourced from Bank Indonesia and the Indonesian Central Bureau of Statistics (BPS). The variables used in this research are time deposits, deposit rates, and inflation in Indonesia. To answer these objectives, this study uses a quantitative descriptive research type with the Vector Error Correction Model (VECM). The research results show that (1) the proportion of time deposits to third party funds in Indonesia in 1995-2021 was 24.33 percent; and (2) Granger causality test results, there is a causal relationship per capita income to 1-month time deposits in Indonesia. The per capita income instrument based on long-term VECM estimation analysis has a significant negative effect with a high coefficient on 1-month time deposits in Indonesia. Meanwhile, short-term research shows that the 1-month time deposit variable has a significant negative effect on the 1-month time deposit variable itself. Based on the results of the Forecast Error Decomposition (FEVD) regression analysis, time deposits have the most significant contribution to time deposits themselves, followed by per capita income, 1-month time deposit interest rates, and inflation.